2009
DOI: 10.1086/648069
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Susceptibility to Infection with DiarrheagenicEscherichia coliamong Infants from Periurban Areas in Lima, Peru

Abstract: Background Diarrheagenic E. coli are being recognized as important pediatric enteropathogens worldwide. However, it is unclear whether there are differences in age-related susceptibility to specific agents, especially among infants. Methods We conducted a passive surveillance diarrhea cohort study of 1034 children from 2 to 12 months of age in Lima, Perú. Control stool samples were collected from randomly selected children without diarrhea. All samples were analyzed for common enteric pathogens and for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
105
4
20

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(154 citation statements)
references
References 36 publications
25
105
4
20
Order By: Relevance
“…This finding is similar to a study we recently conducted in peri-urban districts of Lima, in which we found that diarrheagenic E. coli were the most common pathogens in infants with or without diarrhea (31% and 32%, respectively). 26 Thus, children in Lima are frequently exposed to these bacteria early in life. The interpretation of pathogen frequency in diarrhea versus control samples is complicated.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to a study we recently conducted in peri-urban districts of Lima, in which we found that diarrheagenic E. coli were the most common pathogens in infants with or without diarrhea (31% and 32%, respectively). 26 Thus, children in Lima are frequently exposed to these bacteria early in life. The interpretation of pathogen frequency in diarrhea versus control samples is complicated.…”
Section: Discussionmentioning
confidence: 99%
“…The study population generally belonged to families of low socioeconomic level, mostly living in the suburbs with high growth rates and earning daily income from informal work. We used a modified Vesikari score (17) to determine the severity of an ETEC-associated diarrhea episode. The score included duration of diarrhea (1 to 3 points), maximum frequency of stools per day (0 to 3), maximum frequency of vomits per day (0 to 3), dehydration (0 to 4), treatment by oral or intravenous rehydration (1 to 3), presence of metabolic acidosis (0 to 2,) and electrolytic disequilibrium (0 to 2).…”
Section: Methodsmentioning
confidence: 99%
“…In Bolivia, ETEC has been reported to be present in feces of around 8% of children aged Ͻ5 years hospitalized due to diarrhea (16,17; L. Gonzales, E. Joffre, R. Rivera, Å. Sjöling, A. M. Svennerholm, V. Iñiguez, submitted for publication). However, there is little knowledge of the molecular characteristics and virulence profiles of ETEC in Bolivia.…”
mentioning
confidence: 99%
“…We determined the prevalence of STEC in 3219 samples from children with diarrhoea and 2695 samples from healthy controls without diarrhoea from four prospective cohort studies conducted previously in 2212 Peruvian children aged ,36 months. All studies were in the community setting: three in peri-urban communities of Lima [Villa el Salvador (N. Zavaleta, Instituto de Investigació n Nutricional), Chorrillos (Ochoa et al, 2009) and Independencia (E. Chea-Woo, Universidad Peruana Cayetano Heredia)]; and one in the Andean region of the country [Huaraz (C.F Lanata, Instituto de Investigació n Nutricional)] (Table 1). STEC strains were identified by the presence of stx1, stx2 and eae using a previously validated multiplex real-time PCR system (Guion et al, 2008).…”
Section: Methodsmentioning
confidence: 99%